Increasing the solar share in combined cycles through thermochemical energy storage. (1st February 2021) - Ortiz, C.; Chacartegui, R.; Valverde, J.M.; Carro, A.; Tejada, C.; Valverde, J.
Highlights: A fully novel High Temperature Storage Solar Combined Cycle (HTSSCC) is proposed. Thermochemical energy storage allows a 24 h operation without fuel input. The solar share in the solar combined cycle is highly enhanced (ideally up to 100%). The base case analysed leads to a net solar-to-electric efficiency of 44.5%. Abstract: The integration of Concentrating Solar Power (CSP) in combined cycles is a subjects of increasing attention. Combined cycles require high temperature at the gas turbine inlet (typically over 1000 °C), which hinders plant operation in the absence of direct solar radiation using currently commercial storage technologies based on molten salts (with a temperature limit around 600 °C). Thus, solar power share in current Integrated Solar Combined Cycles (ISCC) is typically lower than 20%, while most of the thermal power required is provided by natural gas. The present manuscript proposes the integration in combined cycles of a Thermochemical Energy Storage (TCES) system based on the Calcium-Looping process, which can release the stored energy at temperatures above 1000 °C. The storage charging step uses the heat provided by a CO2 stream previously heated in a high-temperature solar receiver. The configuration of the solar receiver-calciner is fundamental to determine the amount of storable energy. Results from the conceptual model simulation predict overall plant efficiencies above 45% (excluding solar side losses), suggesting a high potential for the development of this novel integration that would allow enhancing the solar share in combined cycles.